Pengaruh Konsentrasi Palm Oil Mill Effluent (Pome) Dan Komposisi Jumlah Nutrien Untuk Media Kultur Chlorella Pyrenoidosa Sebagai Bahan Baku Biofuel - Erlangga, Herta Furaida; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
utilization of a dynamic world energy consumption in the limitations of fossil energy reserves has created opportunities for the use of microalgae as a biofuel. The use of microalgae as a feedstock source for bioethanol production requires high yields of both biomass and carbohydrates. one of the potentially mikroalga as raw bioetanol is Chlorella pyrenoidosa. Chlorella pyrenoidosa has a carbohydrate content in the cellulose and hemicellulose form in its cell wall which can be utilized for bioethanol production. Palm Oil Mill Effluent (POME) has been studied for their potential as medium growth of microalgae due to high nutrient content. This research was conducted with variation of POME concentration (0; 25; 50; 75 ; 100%v) in medium and addition of synthetic nutrient in the form of urea as nitrogen source and TSP as phosphate source with ratio (2:1 ; 1:2 ; 0,5:1) to enchance the algae growth. The result showed the highest carbohydrate concentration was 184,1 mg/L at cultivation condition of POME concentration 25%v with ratio (urea:TSP) 2:1.Keywords: Chlorella pyrenoidosa, Palm Oil Mill Effluent (POME), Urea, TSP, Carbohydrates